2002
DOI: 10.1262/jrd.48.313
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Release at Fertilization: Artificially Mimicking the Oocyte's Response to Sperm.

Abstract: Abstract. The mechanism of sperm-induced calcium release has been the subject of many studies since the development in the late 1950s of in vitro culture systems that support mammalian fertilization. Despite efforts to elucidate the nature of the signal from the sperm that triggers both the early and late events of oocyte activation, the precise mechanism remains unresolved. Now, with the advent of somatic nuclear transfer technologies, the need to better understand this unique process has been recognised. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 213 publications
(323 reference statements)
1
9
0
3
Order By: Relevance
“…Ethanol-induced Ca 2+ elevation would inactivate the existing CSF and MPF, and the subsequent exposure to protein phosophorylation inhibitor (6-DMAP) would prevent renewal of CSF synthesis in the oocyte and support the further development. Grupen et al (2002) recorded that the kinetics of MPF activity following 6-DMAP treatment was similar to that found in inseminated oocytes. However, compared to 6-DMAP, CHX prolonged the first and shortened the third cell cycle, though cytoskeleton activity was initialized, a large proportion of CHX embryos was unable to accomplished first cleavage (Holm et al 2003).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Ethanol-induced Ca 2+ elevation would inactivate the existing CSF and MPF, and the subsequent exposure to protein phosophorylation inhibitor (6-DMAP) would prevent renewal of CSF synthesis in the oocyte and support the further development. Grupen et al (2002) recorded that the kinetics of MPF activity following 6-DMAP treatment was similar to that found in inseminated oocytes. However, compared to 6-DMAP, CHX prolonged the first and shortened the third cell cycle, though cytoskeleton activity was initialized, a large proportion of CHX embryos was unable to accomplished first cleavage (Holm et al 2003).…”
Section: Discussionsupporting
confidence: 52%
“…Ethanol‐induced Ca 2+ elevation would inactivate the existing CSF and MPF, and the subsequent exposure to protein phosophorylation inhibitor (6‐DMAP) would prevent renewal of CSF synthesis in the oocyte and support the further development. Grupen et al. (2002) recorded that the kinetics of MPF activity following 6‐DMAP treatment was similar to that found in inseminated oocytes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While an increase in the intracellular IP3 mediates Ca 2+ release by binding and gating its receptor on the endoplasmic reticulum membrane [22][23][24], DAG may be involved in the regulation of Ca 2+ influx [25,26]. Similarly, it has been shown that parthenogenetic agents activate oocytes also by inducing intracellular Ca 2+ rises [27][28][29][30][31]. Mature rat eggs showed reduced rates of SA when cultured either in calcium-free medium or in calcium-containing medium with L-type calcium channel blocker or IP3 receptor inhibitor [3,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Suss dan Madison (1983) dalam Gordon (1994) mengemukakan bahwa dari beberapa oosit yang dimaturasi kirakira sekitar 50% diantaranya menunjukkan adanya PB dengan konfigurasi kromosom pada MII. (Grupen et al, 2002) selanjutnya menurun pada saat sel masuk fase anafase I dan fase telofase I tetapi meningkat kembali pada saat sel masuk dalam fase metafase II sebagaimana halnya seperti yang dialami pada saat metafase I. Sementara itu, cyclin B disintesa dan terakumulasi ketika p34 cdc2 ada dalam sitoplasma yaitu pada saat interfase (Solomon et al, 1990dalam Mayes, 2002) dan terdegradasi oleh ubiquitin-dependent proteolysis. Sebaliknya kadar p34 cdc2 tidak berubah selama meiosis (Choi et al, 1991).…”
Section: Hasil Penelitian Dan Pembahasanunclassified